2002
DOI: 10.1152/ajpgi.00343.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric afferent nerves are sensitive to vascular perfusion in a novel preparation of rat ileum in vitro

Abstract: Using novel in vitro preparations of vascularly perfused rat ileum, we investigated mesenteric afferent sensitivity to vascular perfusion. Gut (GPP) and vascular (VPP) perfusion pressures were recorded simultaneously with afferent discharge (AD). After preconstriction (L-phenylephrine), capsaicin (100 microM, gut lumen) caused a transient increase in AD and a sustained fall in VPP, supporting afferent modulation of vascular tone. In turn, AD was affected by vascular perfusion rate (VPR). Increasing VPR step-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…This finding compliments a recent study by Brierley et al (2004), who reported that approximately 50% of hypogastric nerve afferents in the mouse innervate the mesentery surrounding the colon, whereas no mesenteric afferents were observed in the pelvic nerve. Most mesenteric afferents, in this study and others, have been observed near or on blood vessels (Morrison, 1973;Brunsden et al, 2002) and are also known to express CGRP and TRPV1 (Silverman and Kruger, 1988;Stander et al, 2004), which may explain the higher expression of these markers within mouse hypogastric afferents in the current study. Robinson et al (2004) reported slightly higher percentages for TRPV1-positive (82%) and CGRP-positive (81%) mouse colonic afferents, which may be attributable to their larger observed population of colonic afferents within the TL ganglia.…”
Section: Ls;supporting
confidence: 58%
“…This finding compliments a recent study by Brierley et al (2004), who reported that approximately 50% of hypogastric nerve afferents in the mouse innervate the mesentery surrounding the colon, whereas no mesenteric afferents were observed in the pelvic nerve. Most mesenteric afferents, in this study and others, have been observed near or on blood vessels (Morrison, 1973;Brunsden et al, 2002) and are also known to express CGRP and TRPV1 (Silverman and Kruger, 1988;Stander et al, 2004), which may explain the higher expression of these markers within mouse hypogastric afferents in the current study. Robinson et al (2004) reported slightly higher percentages for TRPV1-positive (82%) and CGRP-positive (81%) mouse colonic afferents, which may be attributable to their larger observed population of colonic afferents within the TL ganglia.…”
Section: Ls;supporting
confidence: 58%
“…85 Endings of this type are sensitive to ischaemia, hypoxia and capsaicin, [86][87][88] and they are believed to comprise a major type of nociceptor. They are also sensitive to changes in perfusion rate, with an increased firing rate during reduced flow, 89 although this seems to depend more on mechanical factors than oxygen delivery. 90 Given that these receptors can be activated by blunt probing or compression on the outer wall of the gut, they were initially described as 'serosal' receptors.…”
Section: Type V: Spinal Vascular Afferentsmentioning
confidence: 99%
“…In our previous study (6), we suggested that mesenteric afferents may also sense changes in gastrointestinal blood flow. This sensitivity persisted after removal of the gut itself and, therefore, was a property of the mesenteric membrane and its vascular supply, prior to where they penetrate the gut wall.…”
mentioning
confidence: 89%
“…The terminal ileum (ϳ3 cm rostral to the ileocaecal junction) and the arterial supply were identified, and the vessels were exposed by carefully removing connective tissue from around the superior mesenteric artery and vein. A branching section of an artery with a clear projection to a segment of the ileum was chosen, and unwanted side branches were ligated, as previously described (6).…”
Section: Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation